Mathematics standard level for the IB diploma - Smedley, Robert; Wiseman, Garry (New York : Oxford University Press, 2004)
A comprehensive overview of the material covered in the 2004 standard level mathematics curriculum of the International Baccalaureate Diploma Programme, providing key facts, worked examples, review questions, revision exercises, practice exam papers, and numerical answers.
"2004 curriculum"--Cover.
Includes index.
Adult
Keywords: International baccalaureate -- Study guides; Mathematics -- Examinations -- Study guides; International baccalaureate -- Study guides; Mathematics -- Examinations -- Study guides